Primary Intraosseous Meningioma of the Mandible: CT and MR Imaging Features - Lell, M.; Tudor, C.; Aigner, T.; Kessler, P. (American Journal of Neuroradiology, 2007)
SUMMARY: We describe the rare entity of an intraosseous meningioma arising in the mandible. The meningioma was found incidentally in an asymptomatic adult patient on dental radiography, mimicking other cystic-appearing jaw masses. The CT and MR imaging features of mandibular meningioma are reviewed with reference to prior published descriptions of this unusual entity.